2014
DOI: 10.4236/odem.2014.23006
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Pollution in Work Office: VOCs, Formaldehyde and Ozone by Printer

Abstract: In recent years proof of "indoor air quality", designed to protect and improve the health and safety of workers, was a central strategy in the prevention of many companies. The man creates with the environment in which he lives and works a continuous gas exchange through breathing; this makes the respiratory system main entrance of air pollutants. The indoor pollutants are numerous and originate from different sources. Their concentration may vary over time and depends on the nature of the source, on ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Soon after, Barrero-Moreno et al (2008) measured the gaseous pollutants emitted in a chamber and found the released compounds included styrene, xylenes, ethylbenzene, toluene and particularly, 2,3-dimethyl-2,3-diisobutyl succinonitrile encompassed up to 90% of the VOC identified in the study. Later, Barrese et al (2014) documented O 3 at levels of 45 ppb in an office-sized room and a notable increase in VOC.…”
Section: Resultsmentioning
confidence: 98%
“…Soon after, Barrero-Moreno et al (2008) measured the gaseous pollutants emitted in a chamber and found the released compounds included styrene, xylenes, ethylbenzene, toluene and particularly, 2,3-dimethyl-2,3-diisobutyl succinonitrile encompassed up to 90% of the VOC identified in the study. Later, Barrese et al (2014) documented O 3 at levels of 45 ppb in an office-sized room and a notable increase in VOC.…”
Section: Resultsmentioning
confidence: 98%
“…In this regard, previous studies indicated that formaldehyde, several VOCs, and ozone were emitted during the operation of photocopiers and laser printers. Previous studies showed that formaldehyde and acetaldehyde can be emitted by photocopy machines with substantial emission rates . In addition, considering that laser printers and photocopiers are the major indoor sources of ozone in office environments .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] VOCs are routinely emitted into atmospheric environment from a variety of sources, including combustion processes, industrial processes, traffic exhaust, the emissions from vegetation and animals, and chemicals etc. From the point of view of environmental health and safety, the monitoring and controlling of VOC emissions has become a major current concern with rapid modernization.…”
Section: Introductionmentioning
confidence: 99%